Analysis of the Performance of Moisture Reduction Rate in a Horizontal Mill Type Coffee Dryer Using a Suction Blower - Yanel, Karnova; Hendra, Surya; Saferi, Rozi; Sulaiman, Sulaiman (Universitas Muhammadiyah Jakarta, 2024)
Coffee, originating in the 9th century Ethiopia and later expanding across North Africa and tropical regions globally, remains a crucial commodity. Indonesia, recognized for its robust coffee industry, ranks third worldwide in production, contributing 8% of the global supply. However, the drying process poses challenges to Indonesian farmers due to traditional methods and variable weather conditions. This research aims to evaluate a coffee dryer utilizing forced convection with a suction blower to optimize drying parameters for coffee beans. The study employs a horizontal mill dryer with a heated drum for drying experiments. Results demonstrate that the dryer effectively reduces the moisture content of post-harvest coffee cherries to 2%. In the initial test, 20 kg of coffee dried over 7.5 hours at 75℃ decreased from 61.66% to 5.3% moisture, while a subsequent test with 17 kg dried over 4 hours reduced from 36% to 2% moisture content. The findings conclude that the suction blower-equipped dryer meets Indonesian National Standards (SNI), achieving the requisite 12% moisture content for post-harvest coffee.